A continuum model for intralaminar damage progression and delamination in layered composites. Issue 1 (15th March 2018) - Höwer, Daniel; Stier, Bertram; Bednarcyk, Brett A.; Fish, Jacob; Reese, Stefanie; Simon, Jaan‐Willem
Abstract: The accurate prediction of progressive damage is one of the key challenges in the design of layerd composites. To this end, a continuum damage model has been proposed recently, which can account for both inter‐ and intralaminar damage. This is accomplished by a modification of the damage interaction parameters. The procedure is applied to the example of a [0/90/0] carbon fiber reinforced cross‐ply. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)